please help quickly :3 thanks
![please help quickly 3 thanks class=](https://us-static.z-dn.net/files/ddc/1c0d0ca453fdcc289fc9d16a4d14db88.png)
![please help quickly 3 thanks class=](https://us-static.z-dn.net/files/dc7/b28cc6c600e0472570a06e4541f65d68.png)
6x - 2 = 5x + 3 6x - 5x = 3 + 2 X = 5 9 - 3x = 0 9 = 3x X = 9/3 X = 3
Answer one,
Explanation One,
6 x 5 - 2 = 5 x 5 + 3
30 - 2 = 25 + 3
28 = 28
Answer Two,
Explanation Two,
3/3 + 5 = 6
1 + 5 = 6
So, A is correct,
2 x 3 + 4 = 10
6 + 4 = 10
So, C is correct,
9 - 3 x 3 = 0
9 - 9 = 0
So, F is correct
Hope this helps :-)